An analysis of the burden of migraine and tension-type headache across the global, China, the United States, India and Japan - Xu, Rongjiang; Zhang, Ruonan; Dong, Liang; Xu, Xiaonuo; Fan, Xiaoping; Zhou, Jiying (Frontiers in Pain Research, 2025)
BackgroundRecurrent headaches in headache disorders adversely impact quality of life and job. Migraines and tension-type headache TTH) are the most common primary headaches and a prominent cause of disability globally. However, few research compare headache illness burden in China, India, the United States (US), and Japan.MethodsGlobal and Chinese, the US, Indian, and Japanese migraine and TTH incidence, prevalence, and disability-adjusted life years were taken from the GBD database for 1990–2021. The data is studied utilizing decomposition analysis, health inequality research, joinpoint regression model, and Bayesian Average Annual Percentage Change (BAPC) model.ResultsThe study found that migraine mostly affects women aged 15–49, while TTH are evenly distributed across gender and age. The worldwide average annual percentage change (AAPC) in disease-adjusted life years (DALYs) for migraine and TTH from 1990 to 2021 was 0.0357, a statistically significant trend (p < 0.001), as determined using joinpoint analysis. China exhibited the quickest rise in migraine and TTH incidence and prevalence, as well as the age-standardized rate (ASR) of DALYs, of the four nations analyzed. The US had the highest value of these indicators. Forecasting models reveal that without policy action, migraine prevalence will grow but TTH prevalence would stay unchanged. Decomposition research showed that population expansion is the major cause of migraines and TTH, which will be slightly alleviated by population aging. Health disparities across economic growth areas lessened between 1990 and 2021, according to the report.ConclusionGlobally and in China, migraine and TTH incidence and burden have increased since 1990. Migraines are becoming more common in young and middle-aged women, so headache treatment professionals should invest more in patient education to raise awareness and improve self-management to reduce disease burden and medical costs.